Stored Charge and its Influence on Properties of Anodic Alumina Films - Vrublevsky, Igor; Chernyakova, Katsiaryna; Karpicz, Renata; Jagminas, Arunas (Current Nanoscience, 2019)
In porous and barrier-type anodic alumina films, the stored charge has electronic nature and it plays a significant role in the process of aluminum anodizing. The charge stored can modify the distribution of local field generated by a voltage applied and thus it can affect the oxide growth. The method for the investigation of thermally activated defects in anodic alumina films by reanodizing technique was also described. It was applied for computation of activation energy of electron traps in barrier layer for sulfuric and oxalic acid alumina films and concentration of the traps.
Keywords: electron injection